Investigation of a new porous glass ceramic for potential bone implant - Al-Khateeb, Khalid A. Saeed; Mustafa, Ammar A.; Ismail, Ahmad Faris; Sutjipto, Agus Geter Edy (2011)
A new experimental porous glass ceramic coating for dental implants was prepared with a new formula consisted of a sintered glass ceramic based on alumina, silica glass and boron trioxide. The resultant sintered objects were anodized by one step anodization method at a constant potential of 40V and at a temperature of 22°C. X-ray diffraction analysis was performed to investigate the phase structure of the new material in addition to SEM investigation for surface texture and pores size and distribution. The new experimental material was subjected to failure under universal testing machine for compressive strength. The results showed a promising material to use as coating for implants as X-ray diffraction exhibited an amorphous phase diagram for the material structure whereas SEM results revealed that the pores in the specimens prepared by anodization method were highly ordered and the mean average pore size was 6.5-8.5 nm. The compressive strength test showed that the test-porous glass ceramic coating has a mean numerical value of up to 7.5 MPa which indicates an ambitious result for the new material.